Sous-métis d’Australie. Sort des métis issus d’unions entre Aborigènes et Asiatiques jusque dans les premiers temps de la Fédération - Martine Piquet (Revue Française de Civilisation Britannique)
For a long period of its short history, most particularly during the founding years of the Commonwealth, Australia thought of itself as a “British” nation of the Antipodes. Ideally, the so-called “White Australia Policy” was meant to bar the access of its territory to immigrants other than from the British Isles, and to gradually dilute the Aboriginal minority, both genetically and culturally into white society. This, however, eventually proved impossible to achieve as times were changing and Australia increasingly found it had no choice but to let come the immigrants it needed from other parts of the world (Eastern and Southern Europe, then Asia). The 1997 Bringing Them Home Report on the “Stolen Generations” of children forcibly removed from their families to be “civilised” by religious or state institutions illustrated one of the most scandalous aspects of the way in which half-caste children were treated. Most of those were children with a white parentage. However, and although those facts were often more or less deliberately ignored until recently, Aboriginal people had entertained contacts with their northern neighbours before the arrival of the first white settlers, and there had been a substantial Asian immigration since the XIXth century. Half-castes of Aboriginal and Asian descent were doubly stigmatised by the prejudices against both races. The specific difficulties they met before they could be regarded as citizens are very typical of the deep reject of otherness among Australian society, until the official adoption of multicultural policies in the 1970s.